Evaluating the potential of geopolymer concrete as a sustainable alternative for thin white-topping pavement - S., Sathvik; Shakor, Pshtiwan; Hasan, Sarwar; Awuzie, Bankole Osita; Singh, Atul Kumar; Rauniyar, Abishek; Karakouzian, Moses (Frontiers in Materials, 2023)
The construction industry uses a large quantity of natural materials in the production of concrete. Although attempts to incorporate green materials in concrete began years ago, not every building uses such materials today, and roadways particularly still rely on unsustainable materials. Therefore, this study employed alternative materials, including fly ash, manufactured sand aggregates, and different molarities of alkaline activators, to incorporate waste byproducts in a geopolymer concrete white-topping pavement layer. Recent developments have led to the emergence of geopolymers as distinct classes of materials. In the 1990s, fly ash-based geopolymers became more popular than other kinds, as they are more efficient compared to Portland cement concrete. Aluminosilicate gel can be made by combining fly ash and alkaline solution. A comprehensive literature review of geopolymer concrete was conducted in this study. It examines its critical design parameters, including alkaline solutions, curing temperatures, curing methods, workability, and compressive strength under various environmental conditions. This review provides a unique opportunity for researchers to understand how geopolymer concrete performs. A range of conditions were investigated to determine how to enhance and use this material in a variety of ways. The fresh characteristics of the different mixes were studied using slump and Vee-Bee tests and the characteristics of the cured concrete mixes were determined using flexural, compressive, and flexural fatigue tests. The results indicated that the use of manufactured sand and fly ash with high-molarity alkaline activators realizes a geopolymer concrete with an excellent maximum resistance of 5.1 N/mm2 workability, strength, and fatigue properties, making it suitable for use in roadway pavement.